2007
DOI: 10.1038/sj.eye.6703026
|View full text |Cite
|
Sign up to set email alerts
|

Pain response and follow-up of patients undergoing panretinal laser photocoagulation with reduced exposure times

Abstract: Shortening exposure time of retinal laser is significantly less painful but equally effective as conventional parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 14 publications
2
65
1
6
Order By: Relevance
“…The application of confluent PRP is outwith the current Royal College of Ophthalmologists recommended laser treatment guidelines. 21 Despite an absence of previous published reports for long-term outcomes following Pascal 20 ms PRP in PDR, a study by Al-Hussainy and co-workers 22 in Birmingham (UK) investigated 20 ms PRP using a conventional frequency-doubled neodymium-doped yttrium aluminium garnet system. This paper mainly highlights reduced pain responses, and we have analysed the laser dosage and follow-up data described in the article.…”
Section: -19mentioning
confidence: 99%
“…The application of confluent PRP is outwith the current Royal College of Ophthalmologists recommended laser treatment guidelines. 21 Despite an absence of previous published reports for long-term outcomes following Pascal 20 ms PRP in PDR, a study by Al-Hussainy and co-workers 22 in Birmingham (UK) investigated 20 ms PRP using a conventional frequency-doubled neodymium-doped yttrium aluminium garnet system. This paper mainly highlights reduced pain responses, and we have analysed the laser dosage and follow-up data described in the article.…”
Section: -19mentioning
confidence: 99%
“…Novel laser treatment systems, however, use the multi-shot mode with short pulse duration, thereby providing shorter, less demanding, and less painful treatment sessions (16) . Furthermore, studies have shown that a short pulse duration does not negatively influence PRP treatment efficacy (16)(17)(18) . Targeting the retinal pigment epithelium while preserving adja cent photoreceptors through micro-air bubble formation formed around melanosomes is a novel target therapy modality of laser photocoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…The critical threshold between thermal and mechanical damage is 50 ms (19)(20)(21) . Owing to the use of shorter pulses, novel laser therapy techniques cause only mechanical but not thermal damage, limiting the damage to the retinal pigment epithelium and preserving the inner retinal layers and sensory-rich chorioretinal tissues (17) . Consequently, patients usually report less pain, most probably because retinal sensitivity is better preserved as compared with pain in conservative approaches (9,17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 More recent advances have continued to improve the experience of patients undergoing retinal laser photocoagulation by using pattern scanning laser machines, which allow ophthalmologists to perform the treatment much quicker and with less discomfort. 66 …”
Section: Diabetic Retinopathymentioning
confidence: 99%